PENGARUH MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS IV SDN LARANGAN 09 KOTA TANGERANG - Nazwakhairy Putri Syahra; Ina Magdalena; Sumiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted using a quantitative approach with a quasi-experimental technique. Data were obtained through several procedures, including tests, observations, interviews, and documentation. The subjects of the documentation in this study were fourth-grade students at SD Negeri Larangan 09, Tangerang City. The results of the study revealed that the use of serial picture media in the fourth-grade class at SD Negeri Larangan 09, Tangerang City, could enhance students’ learning engagement. Students appeared more enthusiastic, showed a high interest in composing essays, and actively participated in narrative writing activities. Moreover, the use of serial picture media proved effective in improving narrative writing skills while fostering positive collaborative writing during the learning process. For teachers, the utilization of this media supports their performance and simultaneously enhances professionalism in teaching activities. Therefore, serial picture media can be used as an effective learning tool to develop students’ cognitive (thinking), affective (attitude), and psychomotor (narrative writing skills) aspects. This study recommends that serial picture media be utilized by teachers, students, schools, and future researchers in learning activities, especially in Indonesian language lessons.